Reducción de la prevalencia del bullying en alumnos de secundaria: intervenciones efectivas - Corzo Calderón, Luis Enrique (2022)
Bullying, due to its characteristics and presence in educational environments, continues to be a priority to work on; however, few studies have managed to recognize effective programs to reduce its prevalence. It is for this reason that the objective of this work is to identify effective intervention programs that generate a decrease in the prevalence of bullying in secondary students. Different programs of recent years are reviewed to investigate their effectiveness and usefulness for the educational community. The databases consulted were Scopus and Proquest. For the analysis of the results, investigations that meet the inclusion and exclusion criteria (n = 14) were selected. As a result, it is found that there are effective programs to reduce the prevalence of bullying and that the most worked variables are coping strategies, empathy and socio-emotional and socio-cognitive skills. Regarding the level of evidence, all of them have an experimental or quasi-experimental design. No research applied to the Peruvian context was found, so the urgency that exists in being able to apply this type of intervention based on our reality and educational context is evident.